2021
DOI: 10.21203/rs.3.rs-886517/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Prolonged Face Mask Wearing On Tear Break-Up Time and Dry Eye Symptoms in Health Care Professionals

Abstract: Purpose To evaluate the impact of prolonged surgical face mask wearing on dry eye symptoms and tear film break-up time (T-BUT) in health care professionals. Materials and Methods A total of 33 health care professionals were included in this cross sectional, prospective study. T-BUT measurements were performed twice for all participants in the morning (8 am) and in the afternoon (5 pm) in addition to a complete ophthalmological examination. The subjects also filled-in the ocular surface disease index (OSDI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…A small sample study measured respirator related OSDI scores for health workers that were higher than our average ,the mean OSDI score in the morning was 20.1 ± 8.3 (0-68.75), which signi cantly increased to 27.4 ± 10.4 at the end of the work-day (0-81.25) [20]. Scalinci SZ's Research has shown that health workers and people who need to wear masks for at least 6 hours a day (At least 5 days a week during the 60 days prior) the highest absolute increase was: +12.50.)…”
mentioning
confidence: 59%
“…A small sample study measured respirator related OSDI scores for health workers that were higher than our average ,the mean OSDI score in the morning was 20.1 ± 8.3 (0-68.75), which signi cantly increased to 27.4 ± 10.4 at the end of the work-day (0-81.25) [20]. Scalinci SZ's Research has shown that health workers and people who need to wear masks for at least 6 hours a day (At least 5 days a week during the 60 days prior) the highest absolute increase was: +12.50.)…”
mentioning
confidence: 59%
“…The variables associated with a logistic regression model were screen time, female sex, refractive surgery, rosacea, depression, previous dry eye disease, keratoconus and blepharitis. The positive effects of telework include comfortable air conditioning in the home environment and working without face mask to avoid mask-associated DE [5][6][7][8][9][10].…”
Section: Plos Onementioning
confidence: 99%
“…Many medical problems and ocular manifestations related to COVID-19 have been documented, including conjunctivitis, uveitis and neuro-ophthalmological disorders [2][3][4]. In addition, mask-associated dry eye [5][6][7][8][9][10], presbyopia [11] and digital eye strain [12] have been observed. Due to the government's recommendation to telework, many companies shifted to working from home, resulting in increased screen time and general fatigue [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The tear film parameters worsen as the duration of wearing the mask increases [43]. Wearing the face mask for a long duration (e.g., more than 8 h) leads to an increase in dry eye symptoms that were detected using the OSDI a significant (p = 0.01) decrease in the TBUT [44]. Clearly, wearing a face mask for long duration has a negative effect on the tear film and daily life activities [45][46][47].…”
Section: Plos Onementioning
confidence: 99%